An in-line fiber-optic modal interferometer for simultaneous measurement of twist and ambient temperature - Yongqin Yu; Quandong Huang; Xuejin Li; Xue Chen; Chenlin Du (Sensing and Bio-Sensing Research, 2014)
A novel and simple sensor based on fiber-optic modal interferometer fabricated by a segment of low elliptical hollow-core photonic bandgap fiber for simultaneous temperature and twist measurements is demonstrated. Meanwhile the sensor can also measure the twist angle and determine the twist direction simultaneously. The mode distribution of EHC-PBGF is demonstrated both in theory and experiments. There is an obvious difference of two transmission dips on the temperature and twist. The twist sensitivities of Dip 1 and Dip 2 are obtained to be −31.95 and −585.8 pm/(rad/m), respectively. The temperature sensitivities are 12.99 pm/°C for Dip 1 and 5.09 pm/°C for Dip 2, respectively. Two parameters of twist and temperature can be distinguished and measured simultaneously by using a sensing matrix. Meanwhile the structure is found to be weakly sensitive to the axial strain. It has the advantage of avoiding the crosstalk of strain in the applications.